Sistem Informasi Manajemen Pendidikan Dalam Meningkatkan Pendaftaran Siswa Baru - Danang Dwi Prasetyo; Nur Wahyuningsih (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This Study aims to determine the education management information system and the School’s efforts to increase the acceptance of new students at SD Muhammadiyah Parakan Temanggung. This Type of research uses qualitative data collection methods through observation, interviews, and documentation. The data analysis technique uses the Triangulation technique. The results showed that the education Information System was based on student management so it was easy to record. Students data input operators can be directly accessed. Through the internet and wifi so that anyone who will see it can be accessed easily and quickly. The school’s efforts to increase the acceptance of new student registration through an information system, namely using a good school image. Optimizing the advantages of the quality of school education. Through social media and printing, for example comparative study abroad and various  national level Olympic Champions.